Tersandera di usia belia: Fenomena pernikahan usia dini serta implikasinya terhadap pendidikan, sosial dan kesehatan mental anak (studi kasus kabupaten malang) - Maghfiroh, Siti Awaliatul (Maliki Interdisciplinary Journal, 2025)
In the perspective of Islam, marriage is regarded as a mitsaqan ghalizha (a strong covenant) between a man and a woman to establish a household based on sakinah, mawaddah, and rahmah. Therefore, marriage is not only viewed as a physical and emotional bond, but also as a form of worship aimed at preserving dignity and ensuring the continuity of generations. In general, marriage is essentially an institution intended for individuals who are ready both physically, psychologically, and socially. However, in reality, the phenomenon of early marriage is still widely found, including in Malang Regency. Early-age marriage gives rise to various problems, particularly those related to the continuation of children’s education and their social life within society. Frequently, education is disrupted or even terminated, leading to long-term impacts on the quality of human resources. Moreover, this phenomenon also affects social dynamics, ranging from role adjustment, economic burdens, to vulnerability to domestic conflict. This study employs a qualitative descriptive method with secondary (literature-based) data to explore how the phenomenon of early marriage occurs and what implications it has for education and social life in Malang Regency. The aim of this study is to provide a deeper understanding of the consequences of early-age marriage practices, as well as to serve as a reflection for society and policymakers in formulating preventive measures and appropriate solutions.